Changes in Ground Temperature and Dynamics in Mountain Permafrost in the Swiss Alps - Haberkorn, Anna; Kenner, Robert; Noetzli, Jeannette; Phillips, Marcia (Frontiers in Earth Science, 2021)
Rising air temperatures and increasingly intense precipitation are being observed in the Swiss Alps. These changes strongly affect the evolution of the temperature regime and the dynamics of mountain permafrost. Changes occur at different rates depending on ground ice content. Long-term monitoring reveals progressive warming and degradation of permafrost and accelerating rock glacier velocities. This study analyses changes occurring in ice-rich (excess-ice) and ice-poor mountain permafrost in Switzerland between 1997 and 2019 on the basis of ground temperature and rock glacier dynamics measurements carried out by the WSL Institute for Snow and Avalanche Research SLF at seven sites. Long-term borehole data indicate an increase of ground temperatures at all depths, in particular at ice-poor and nearly snow-free sites. Active layers are thickening at most sites and prolonged periods of active layer thaw are observed. Long autumn zero curtains are observed in ice-rich permafrost, possibly leading to an overall acceleration of rock glaciers. All these changes point towards ongoing permafrost warming and permafrost degradation in future.